Teachers’ Adaptive Agency in Project-Based Learning: Belief–Practice Alignment in Secondary Education - Novika Amalia; Richard Ferry Nugraha; Muhammad Subhan Fikri; Emeral Emeral; Dellis Pratika; Bahing Bahing (Universitas Hamzanwadi, 2025)
Project-Based Learning (PjBL) has been widely promoted as a student-centered pedagogy that supports the development of 21st-century skills; however, its effectiveness depends largely on how teachers’ beliefs are translated into classroom practice. This study examines high school teachers’ beliefs and practices related to PjBL across three interconnected dimensions: professional development (training), classroom implementation, and reflection. Employing an explanatory sequential mixed-methods design, quantitative data were collected through a questionnaire administered to 36 high school teachers in Katingan Regency, Central Kalimantan, followed by semi-structured interviews with three selected participants to explore belief–practice alignment and contextual influences in greater depth. Quantitative findings revealed consistently high mean scores for both beliefs and practices across all three dimensions, indicating a generally strong alignment between teachers’ conceptual endorsement of PjBL and their reported enactment. However, areas of partial misalignment emerged in practices requiring sustained autonomy and long-term pedagogical change, particularly self-directed professional development, facilitation of student agency and project authenticity, and the systematic integration of reflective insights into future lesson planning. Qualitative findings confirmed that while teachers value PjBL and adapt it flexibly to classroom realities, structural constraints, such as curriculum demands, limited training continuity, and assessment pressures, limit deeper implementation. The study concludes that teachers demonstrate adaptive agency in implementing PjBL, with belief–practice alignment strengthened when supported by institutional facilitation, mentoring, and reflective cultures. Sustained professional development and contextual support are therefore essential to move PjBL beyond procedural adoption toward a more profound, transformative pedagogical practice.